Using biotechnology to enhance host resistance to aflatoxin contaminiation of corn - Brown, R.L.; Zhi-Yuan, C.; Menkir, A.; Cleveland, T.E. (Academic Journals, 2003)
Host resistance is the most widely explored strategy for eliminating aflatoxin contamination by Aspergillus flavus. Breeding strategies for developing resistant corn germplasm have been enhanced by the development of new screening tools for field inoculation and for laboratory screening. RFLP analysis of corn populations has highlighted the possibility that different resistance traits can be successfully pyramided into agronomically useful germplasm, while proteomics has impacted the identification of proteins associated with resistance (RAPs). The identification of RAPs has also been enhanced by the discovery of near-isogenic corn lines in progeny generated in a West African breeding program. The characterization of genes of the aflatoxin biosynthetic pathway has provided a foundation for a genomics investigation aimed at understanding the biochemical function and genetic regulation of aflatoxin biosynthesis. Successful inhibition of aflatoxin elaboration may require not only the action of antifungal compounds, but of compounds that block biosynthesis of toxins as well.